The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1093/cvr/cvq264
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling during mouse ventricular maturation: a role for miR-27 modulating Mef2c expression

Abstract: our data present a comprehensive profile of microRNA expression during ventricular maturation, providing an entry point for investigation of the functional roles of the most abundantly and differentially expressed microRNAs during cardiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 36 publications
4
90
0
1
Order By: Relevance
“…Thus, additional studies are required to determine whether this slight derepression of PPAR-␥ by miR-27 inhibition contributes to the pro-angiogenic effects of the miR. Other potential targets contributing to the pro-angiogenic effect of miR-27 might be the lymphangiogenic growth factor VEGF-C, which is an in silico predicted target of miR-27, or the transcription factor MEF2C, which is targeted by miR-27 in cardiomyocytes 25 and regulates vascular integrity and angiogenesis. 50 Whereas VEGF-C was significantly up-regulated in antagomir-27a/btreated mice, the expression of MEF2C was not regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, additional studies are required to determine whether this slight derepression of PPAR-␥ by miR-27 inhibition contributes to the pro-angiogenic effects of the miR. Other potential targets contributing to the pro-angiogenic effect of miR-27 might be the lymphangiogenic growth factor VEGF-C, which is an in silico predicted target of miR-27, or the transcription factor MEF2C, which is targeted by miR-27 in cardiomyocytes 25 and regulates vascular integrity and angiogenesis. 50 Whereas VEGF-C was significantly up-regulated in antagomir-27a/btreated mice, the expression of MEF2C was not regulated.…”
Section: Discussionmentioning
confidence: 99%
“…24 The myocyte enhancer factor 2C (MEF2C) is another important target of miR-27b during heart development. 25 However, the specific functions and targets of miR-27 in endothelial cells are largely unexplored. As the family members miR-27a and miR-27b differ in only one nucleotide and share the same seed sequence, we investigated the specific role of both family members for the angiogenic activity of endothelial cells and determined the effects on neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analysis revealed two binding sites in miR-27b and the MCP1 3'-UTR. The literature reports that miR-27b affects the function of MCP1 by acting on certain target genes in myocardial cells (Chinchilla et al, 2011;Wang et al, 2012), but there have been no reports on whether miR-27b downregulates the expression of MCP1 and is involved in the occurrence and development of VMC. Therefore, in this study, we used IL-17 to induce the upregulation of MCP1 expression, then up-regulated the content of miR-27b by transiently transfecting H9C2 cells with miR-27b mimics.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of expression patterns for the Pitx2 isoforms during heart development has been characterized in zebrafish, chicken and mouse (Campione et al, 1999;Campione et al, 2001; Franco et al, 2003) These studies have pointed out that Pitx2c plays a determinant role in left-right signalling during cardiogenesis (Campione et al, 1999;Schweickert et al, 2000;Liu et al, 2001). In addition, a molecular 248 F. Hernandez-Torres et al link between Pitx2c and AF has been recently reported (Chinchilla et al, 2011;Kirchhof et al, 2011;Wang et al, 2010). Taken together, all these data suggest an important role of Pitx2c in heart development and homeostasis.…”
Section: Abstract: Pitx2 Isoforms Heart Development Mouse and Ventmentioning
confidence: 71%
“…In addition, we cannot rule out the possibility that different PITX2 isoforms could be coexpressed in the same cardiac cells, according to the fact that different isoforms of PITX2 can act together forming homo and heterodimers leading to transcriptional synergism (Cox et al, 2002;Saadi et al, 2003). Current studies suggest that Pitx2-mediated signalling during cardiogenesis is conducted within three different cell types: the myocardium, the cardiac neural crest (CNC) cells, and the pharyngeal arch mesenchyme (Campione et al, 1999;Chinchilla et al, 2011; Franco et al, 2003;Kioussi et al, 2002;Liu et al, 2002;Tessari et al, 2008), minimizing the possible role that Pitx2 a, b or c, may have during development of epicardial and endocardial derivatives. In addition, it was previously reported only that Pitx2c expression is never detected in endocardium (Liu et al, 2002).…”
mentioning
confidence: 99%